Measuring the Power of Undervalued Currency to Stimulate Exports - Edelberg, Victor; Krishnaswami, A. (Review of Economic Studies, 1937)
Victor Edelberg, A. Krishnaswami; Measuring the Power of Undervalued Currency to stimulate Exports, The Review of Economic Studies, Volume 5, Issue 1, 1 Oc